Diego Rivera : his art, his life - Gonzales, Doreen (Springfield, NJ : Enslow Publishers, 1996)
A biography of the noted Mexican muralist discussing his art, his political ties, and his relationship with the painter Frida Kahlo.
Includes bibliographical references (p. 126) and index.
Keywords: Rivera, Diego, -- 1886-1957 -- Juvenile literature; Rivera, Diego, -- 1886-1957.; Painters -- Mexico -- Biography -- Juvenile literature; Artists